INFORMATION SYSTEM IN RAW MATERIAL SUPPLY PT Tuntex USING VISUAL BASIC 6.0. - Tety TRISNAYANTI; Elly Agustina J., SKom, MMSI (Jurnal Sistem Informasi, 2005)
PT. Tuntex is a company engaged in the textile, in the process of production of PT. Tuntex uses three types of raw materials Wool, Foy (FULL ORIENTED yare) and Poy (Pree ORIENTEDYARE)  three  types  of  these  materials  have  a  variety  of  types  which  will  be combined with each type of different raw materials becoming a cloth with the flexible nature of berpariasi. The type of yarn that will be used is Foy, because of the string can not be pulled or wrinkle that can produce a strong fabric. Meanwhile, Poy yarn types can be processed into a flexible material and soft no heat easily, therefore the two types of raw materials can be incorporated in the processing will produce the best quality fabrics.